2012
DOI: 10.14306/renhyd.16.2.94
|View full text |Cite
|
Sign up to set email alerts
|

Can Flaxseed Help Satisfy Appetite in Women Subjected to Bariatric Surgery?

Abstract: Antecedentes: Se considera que la cirugía bariátrica es el método inmediato más eficaz para la pérdida de peso en la obesidad mórbida a pesar de observarse, en algunos casos, la recuperación del peso corporal después de algunos años. El control del apetito, la saciedad y la satisfacción son esenciales para que los resultados se mantengan a largo plazo después de la cirugía. La composición de ácidos grasos de la dieta podría ser un factor implicado en la regulación de la saciedad. Debido a que la linaza es un a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Moreover, one study was done on children (Gholami & Akhlaghi, 2021), while the other's participants were adults. As presented in Table 1, four studies were conducted in Brazil (Candido et al, 2018; Cohen et al, 2013; Cosendey Menegati et al, 2012; Monteiro et al, 2016), three in Denmark (Ibrugger et al, 2012; Kristensen et al, 2012, 2013), two in the UK (Almehmadi et al, 2018; Lakhani & Ibrahim, 2016), and one study in each country of USA (Lafond et al, 2015), India (Kapoor et al, 2017), Iran (Gholami & Akhlaghi, 2021), and Canada (Vuksan et al, 2017). In different studies, the sample size of the intervention group ranged from 6 to 65 and the mean age of the intervention group ranged from 22.5 to 48.3 years old in adults studies and 11.5 years old in the study done on children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, one study was done on children (Gholami & Akhlaghi, 2021), while the other's participants were adults. As presented in Table 1, four studies were conducted in Brazil (Candido et al, 2018; Cohen et al, 2013; Cosendey Menegati et al, 2012; Monteiro et al, 2016), three in Denmark (Ibrugger et al, 2012; Kristensen et al, 2012, 2013), two in the UK (Almehmadi et al, 2018; Lakhani & Ibrahim, 2016), and one study in each country of USA (Lafond et al, 2015), India (Kapoor et al, 2017), Iran (Gholami & Akhlaghi, 2021), and Canada (Vuksan et al, 2017). In different studies, the sample size of the intervention group ranged from 6 to 65 and the mean age of the intervention group ranged from 22.5 to 48.3 years old in adults studies and 11.5 years old in the study done on children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies have examined the effect of flaxseed supplementation on satiety (Almehmadi et al, 2018; Cohen et al, 2013; Cosendey Menegati et al, 2012; Ibrugger et al, 2012; Kristensen et al, 2012, 2013; Lakhani & Ibrahim, 2016; Monteiro et al, 2016). Three of these studies showed a significant satiety increase (Ibrugger et al, 2012; Kristensen et al, 2013; Monteiro et al, 2016), while the others found no significant effect on this variable (Almehmadi et al, 2018; Cohen et al, 2013; Cosendey Menegati et al, 2012; Kristensen et al, 2012; Lakhani & Ibrahim, 2016). Monteiro et al found a significant increase in satiety after supplementation with different types of flaxseed and observed a better increasing effect in the overweight ( r : −572, p : .01) and grade‐1 obese women ( r : −467, p : .02) compared to grade‐2 obese participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations